2021
DOI: 10.18502/jmehm.v14i12.7667
|View full text |Cite
|
Sign up to set email alerts
|

Moral distress among Iranian neonatal intensive care units’ health care providers: a multi-center cross sectional study

Abstract: Due to the unique nature of the neonatal intensive care unit (NICU) and its moral distress, this study aimed to investigate moral distress in the NICU. This cross-sectional study was conducted on 234 physicians and nurses working in the neonatal wards of eight hospitals. The Corley’s Moral Distress Scale was used to collect data. Findings showed that 25 of the participants were physicians and 209 were nurses. The intensity and frequency of distress among physicians and nurses were assessed as moderate. The mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
7
1
Order By: Relevance
“…MDS-R scores were slightly lower in physicians than in nurses/physiotherapists, although the difference was not significant. Although this result contrasts with that of some studies which found higher MD levels in nurses than in other professional categories [ 15 , 18 , 26 , 43 , 53 , 54 , 59 ], it is in line with others which instead found no differences in MD levels between physicians and non-physicians [ 36 , 49 , 60 ]. The differences between the various studies may be due to the different social and cultural characteristics of the study samples and the different organizational contexts.…”
Section: Discussioncontrasting
confidence: 99%
“…MDS-R scores were slightly lower in physicians than in nurses/physiotherapists, although the difference was not significant. Although this result contrasts with that of some studies which found higher MD levels in nurses than in other professional categories [ 15 , 18 , 26 , 43 , 53 , 54 , 59 ], it is in line with others which instead found no differences in MD levels between physicians and non-physicians [ 36 , 49 , 60 ]. The differences between the various studies may be due to the different social and cultural characteristics of the study samples and the different organizational contexts.…”
Section: Discussioncontrasting
confidence: 99%
“…However, additional studies are needed to enhance these findings and draw conclusions. Unlike most recent studies on cultural adaptation of MD measurement instruments [ 49 , 50 , 51 , 52 ], which only tested reliability, our one includes in-depth validation analysis with dimensionality and validity tests. We deem it proof to consider the new scale an appropriate measure of MD and a valuable base for further research efforts.…”
Section: Discussionmentioning
confidence: 99%
“…The feeling of unfamiliarity and powerlessness, loss of control, caring for the same patients and having to deal with restrictions have caused nurses to face challenges in implementation of ethical requirements and as a result experience moral distress ( 6 ) . Moral distress is a painful and unstable psychological feeling that occurs when a nurse is fully aware of a moral act, but unable to perform it ( 7 , 8 ) .…”
Section: Introductionmentioning
confidence: 99%
“…The study by Henrich et al showed that moral distress at the individual level causes negative emotional reactions in nurses such as fatigue, embarrassment about not providing good care, inappropriate level of care, worthlessness and discouragement ( 15 ) . Termination of employment in the organization and leaving work are other consequences of moral distress that inflict irreparable damage on the organization and the health service delivery system ( 8 , 16 ) .…”
Section: Introductionmentioning
confidence: 99%